2003
DOI: 10.1111/j.1469-8749.2003.tb00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor recovery in children after traumatic brain injury: analyses of gait, gross motor, and fine motor skills

Abstract: The recovery of gait, gross motor proficiency, and hand function was examined in 23 children (13 males, 10 females; age 4 years 7 months to 15 years 10 months) with traumatic brain injury (TBI) over five months of in patient rehabilitation. We used gait analysis, the Gross Motor Function Measure, the Developmental Hand Function Test, and the Purdue Pegboard test. Brain injury had been severe (initial Glasgow Coma Scale GCS <8) in 17 children and moderate (GCS 8–10) in six children. Compared with healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 36 publications
3
30
2
Order By: Relevance
“…This is in agreement with previous studies (Teasdale et al, 1979;Authier et al, 1995) suggesting that there is a plausible effect of age and functional recovery, as youth plays a prominent factor in neuroplasticity following brain injury (Uswatte and Taub, 2010;Rutović et al, 2019). Additionally, other studies have shown that, depending on the severity of spasticity, some patients might demonstrate significant gait recovery levels (e.g., increased walking velocity) while other might show minimal improvements (Knutsson and Richards, 1979;Kuhtz-Buschbeck et al, 2003;Watson and Hitchcock, 2004;Tilson et al, 2010;Jang and Kwon, 2016;Marque et al, 2019), as observed postoperatively in SP1. Even though the joint kinematic parameters of the lower limbs in SP1 didn't show outstanding improvements over time, at 12 months postoperatively the patient was able to ambulate comfortably with a cane; no longer relying on a wheelchair.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with previous studies (Teasdale et al, 1979;Authier et al, 1995) suggesting that there is a plausible effect of age and functional recovery, as youth plays a prominent factor in neuroplasticity following brain injury (Uswatte and Taub, 2010;Rutović et al, 2019). Additionally, other studies have shown that, depending on the severity of spasticity, some patients might demonstrate significant gait recovery levels (e.g., increased walking velocity) while other might show minimal improvements (Knutsson and Richards, 1979;Kuhtz-Buschbeck et al, 2003;Watson and Hitchcock, 2004;Tilson et al, 2010;Jang and Kwon, 2016;Marque et al, 2019), as observed postoperatively in SP1. Even though the joint kinematic parameters of the lower limbs in SP1 didn't show outstanding improvements over time, at 12 months postoperatively the patient was able to ambulate comfortably with a cane; no longer relying on a wheelchair.…”
Section: Discussionsupporting
confidence: 91%
“…Cognitive deficits include attention and memory deficits, reduction in information processing speed and psychiatric disorders . Motor impairments include deficits in fine motor skills, such as finger‐tapping and grip strength, and coordination, whereby patients have impaired gait and balance . Persistent sensory deficits have been demonstrated extensively across a number of tasks and across modalities .…”
Section: Epidemiology and Clinical Consequences Of Traumatic Brain Inmentioning
confidence: 99%
“…The causes of the prolonged functional deficits in diffuse TBI are rarely known . The absence of obvious cell death and the array of cognitive and memory deficits suggests a substantial but subtle functional alteration with ramifying consequences and one beyond resolution of standard imaging and/or histology. It is worth noting here that TBI‐induced deficits in cognition, memory and movement are invariably viewed as resulting from damage to brain areas specific to those functions.…”
Section: Sensory Deficits May Underlie Behaviour Changes In Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…). Kuhtz‐Buschbeck et al . found that GMFM scores correlated with kinematic measures derived from gait analysis in a sample of 5‐ to 15‐year‐old children rehabilitating from severe TBI.…”
mentioning
confidence: 99%